Incidence of newborn resuscitative interventions at birth and short-term outcomes: a regional population-based study - Knut Øymar; Hege Langli Ersdal; Peder Aleksander Bjorland; Siren Irene Rettedal (BMJ Publishing Group, 2019)
Objectives To determine the incidence and characteristics of resuscitative interventions at different gestational ages and short-term outcomes after resuscitation.Design, setting and patients A prospective observational study in an unselected population at Stavanger University Hospital, Norway, from October 2016 until September 2017.Interventions Using a data collection form and video recordings, we registered and analysed resuscitative interventions.Main outcome measures Incidence of continuous positive airway pressure (CPAP), positive pressure ventilation (PPV), intubation, chest compressions and intravenous fluid or epinephrine boluses. Short-term outcomes of resuscitated newborns.Results All 4693 newborns in the study period were included in the study. Two hundred and ninety-one (6.2%) newborns received interventions in the first minutes of life beyond drying and stimulation. PPV was provided in 170 (3.6%) while CPAP (without PPV) was provided in 121 (2.6%) newborns. Duration of PPV was median (IQR) 106 s (54-221). Intubations were performed in 19 (0.4%) newborns, with a mean (SD) intubation time of 47 (21) s. Ten (0.2%) newborns received chest compressions and epinephrine was administrated in three (0.1%) newborns. Sixty-three per cent of the treated newborns from 34 weeks' gestational age were returned to parental care without further follow-up.Conclusions The need for resuscitative interventions after birth was frequent in this unselected population in a high-resource setting, but full cardiopulmonary resuscitation was rare. Short-term outcomes were good, suggesting that most newborns treated with resuscitative interventions were not severely affected.